Impacto de las tasas de interés de intervención, IBR y DTF en la inflación (junio 2012 - junio 2016) (2018)
The purpose of the work is to develop each of the proposed objectives by investigating the economic environment, the causes and consequences that generated the volatility in the variables to be studied, the intervention interest rate, IBR and DTF, as well as analyzing the impact of these variables on the inflation. To study this impact, it is necessary to evaluate macroeconomic indicators for the period of June 2012 - June 2016, to carry out a descriptive statistical study, by means of statistical models that define the impact of each of the variables on inflation.